Targeting the chemokine receptor CXCR4 with histamine analog to reduce inflammation in juvenile arthritis - Nassima Bekaddour; Nassima Bekaddour; Nikaïa Smith; Benoit Beitz; Alba Llibre; Tom Dott; Anne Baudry; Anne-Sophie Korganow; Anne-Sophie Korganow; Anne-Sophie Korganow; Sébastien Nisole; Richard Mouy; et al. (Frontiers in Immunology, 2023)
IntroductionAmong immune cells, activated monocytes play a detrimental role in chronic and viral-induced inflammatory pathologies, particularly in Juvenile Idiopathic Arthritis (JIA), a childhood rheumatoid arthritis (RA) disease. The uncontrolled activation of monocytes and excessive production of inflammatory factors contribute to the damage of bone-cartilage joints. Despite the moderate beneficial effect of current therapies and clinical trials, there is still a need for alternative strategies targeting monocytes to treat RA.MethodsTo explore such an alternative strategy, we investigated the effects of targeting the CXCR4 receptor using the histamine analog clobenpropit (CB). Monocytes were isolated from the blood and synovial fluids of JIA patients to assess CB's impact on their production of key inflammatory cytokines. Additionally, we administered daily intraperitoneal CB treatment to arthritic mice to evaluate its effects on circulating inflammatory cytokine levels, immune cell infiltrates, joints erosion, and bone resorption, as indicators of disease progression.ResultsOur findings demonstrated that CXCR4 targeting with CB significantly inhibited the spontaneous and induced-production of key inflammatory cytokines by monocytes isolated from JIA patients. Furthermore, CB treatment in a mouse model of collagen-induce arthritis resulted in a significant decrease in circulating inflammatory cytokine levels, immune cell infiltrates, joints erosion, and bone resorption, leading to a reduction in disease progression.DiscussionIn conclusion, targeting CXCR4 with the small amino compound CB shows promise as a therapeutic option for chronic and viral-induced inflammatory diseases, including RA. CB effectively regulated inflammatory cytokine production of monocytes, presenting a potential targeted approach with potential advantages over current therapies. These results warrant further research and clinical trials to explore the full therapeutic potential of targeting CXCR4 with CB-like molecules in the management of various inflammatory diseases.